Accessible Atonement : Disability, Theology, and the Cross of Christ - McLachlan, David, 1963- (Book collections on Project MUSE., 2021)
"Engages systematic theology with pastoral concerns to expand our understanding of Christ's sacrifice so that persons with disabilities are more integrally included in our conceptions of soteriology and ecclesiology, especially liturgy"--